On the Approximation of Zeros of Non-Self Monotone Operators. (2nd June 2016) - Colao, Vittorio; Marino, Giuseppe; Muglia, Luigi
ABSTRACT: In this article, we study the approximation of common zeros of non-self inverse strongly monotone operators defined on a closed convex subset C of a Hilbert space H . For a non-self family of operators, we introduce an iterative algorithm without relying on projections. Approximation of common fixed points for finite families of non-self strict pseudo-contractions in the sense of Browder-Petryshyn is also obtained. The novelty of our algorithm is that the coefficients are not given a priori and no assumptions are made on them, but they are constructed step by step in a natural way.